Pemanfaatan Differential Evolution dalam Optimasi Kebutuhan Gizi Balita Gizi Kurang dan Buruk - Dethan, Sinyo April; Fanggidae, Adriana; Ledoh, Juan Rizky Mannuel; Polly, Yulianto Triwahyuadi (Jurnal Teknik Informatika dan Sistem Informasi, 2026)
Abstract — Malnutrition in toddlers, particularly wasting and severe wasting, remains a significant challenge in Indonesia, particularly in the East Nusa Tenggara (NTT) province. This study aims to develop a daily food menu optimization system for wasted and severely wasted toddlers aged 12-59 months using the Differential Evolution (DE) algorithm. The system is designed to balance macronutrient (energy, protein, fat, carbohydrates, fiber) and micronutrient (calcium, iron, zinc, copper, phosphorus, vitamin C) needs. The utilized database consists of food items commonly found and easily accessible in NTT, categorized into staple foods, side dishes, vegetables, and fruits. The DE algorithm was implemented to generate optimal, varied, and affordable menu combinations. The results show that the DE algorithm successfully created balanced menu recommendations. The optimal configuration was achieved with a population size of 20 and 1,500 iterations, consistently producing valid menu solutions with efficient computation time. This system proves to be an effective tool for addressing toddler nutritional fulfillment by considering local food variety and affordability.